Seroprevalence of Lyme borreliosis in Finland 50 years ago - J. Cuellar; T. Dub; J. Sane; J. Hytönen (Elsevier, 2022)
Objectives
Lyme borreliosis (LB) is a tick-borne infection common in Europe. In Finland, the LB seroprevalence in the healthy population was 3.9% in 2011. While the present-day seroprevalence of LB is well characterized in several European areas, there are no studies on the seroprevalence of LB before the description of the infection in the late 1970s.
Methods
We used a subset of historical serum samples (n = 994) collected during the Finnish Mobile Clinic Health Survey, a nationwide cross-sectional health survey of the 1960s and 1970s. All samples were screened with Borrelia burgdorferi whole-cell sonicate IgG ELISA. The seropositivity of the samples was further confirmed by the C6 peptide ELISA and recomBead IgG 2.0 bead immunoassay. The association of LB seropositivity with risk factors and with self-reported diseases and symptoms relating to disseminated LB were analysed by logistic regression.
Results
B. burgdorferi IgGs were detected in 199 of 994 analysed samples; hence, the overall seroprevalence was 20.0% (95% confidence interval: 17.6–22.6). The highest seroprevalence was observed in persons aged ≥50 years (165/696), in those currently not working (92/383), and in the regions of South and Central Finland (91/226 and 27/88, respectively). Further, perception of feeling unhealthy (129/197 versus 412/794) was higher among LB-seropositive individuals compared to LB-seronegative participants.
Conclusion
LB seroprevalence was considerably higher in Finland in the late 1960s and early 1970s than in 2011. This result questions the perception of an unprecedentedly high LB seroprevalence in present-day Europe.